articel ASSESSING THE ROLE OF COST ACCOUNTING IN IMPROVING OPERATIONAL EFFICIENCY IN MANUFACTURING FIRMS - Ricky Agusiady; Nia Riana; Zaenal Aripin (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background:Cost accounting plays a pivotal role in the manufacturing industry by helping firms control costs, enhance profitability, and improve operational efficiency. With the increasing pressure on manufacturing firms to remain competitive, efficient, and cost-effective, the strategic use of cost accounting is essential for decision-making and performance management. Aims:This study aims to evaluate the impact of cost accounting practices on the operational efficiency of manufacturing firms. Specifically, it seeks to identify how cost accounting techniques contribute to better cost control, process optimization, and resource allocation, thereby improving overall operational performance. Research Method:A mixed-method approach is employed in this study, combining qualitative and quantitative research methods. Data is gathered from manufacturing firms through surveys, interviews, and case studies to assess the role of cost accounting in improving operational efficiency. Statistical analysis is used to examine the relationship between cost accounting practices and operational outcomes. Results and Conclusion:The findings indicate that cost accounting significantly contributes to operational efficiency by enabling firms to identify inefficiencies, optimize resource usage, and make informed decisions. Firms that implement cost accounting techniques such as activity-based costing (ABC), standard costing, and variance analysis show improved cost management and enhanced productivity. Contribution:This study provides valuable insights into the practical application of cost accounting in the manufacturing sector, offering recommendations for firms to optimize their cost accounting systems for better operational efficiency.